Pelatihan Smart Research Writing: Transformasi Digital dalam Penulisan Tugas Akhir Mahasiswa STIE Galileo Batam - Hielvita Ludiya; Setyo Widiarto; Priyanto Priyanto; Sulih Wahyudiono (Universitas Pahlawan Tuanku Tambusai, 2026)
Scientific writing is a fundamental competency for students, but technical challenges in managing references and formatting manuscripts often hinder the completion of final assignments. This Community Service Activity aims to improve digital literacy and technical skills of STIE Galileo Batam students through